Synthesis and Characterization of Copper(II) Sulphate complexes with 2-, 3-and 4-Cyano-Pyridines and Anilines - Ahuja, I.S.; Tripathi, Shailendra; Yadava, C.L. (Asian Journal of Chemistry, 2010)
Coordination compounds of copper(II) sulphate with 2-, 3- and 4- cyano-pyridines and anilines have been synthesized and characterized on the basis of analytical data, molecular conductance, magnetic susceptibilities, electronic and infrared spectral measurements. Tentative coordination numbers and stereochemical environments around copper(II) are discussed in each case.